Construction manager's (CMs) skills and project performance / Irewolede Ijaola and Olabode Ogunsanmi. - Ijaola, Irewolede; Ogunsanmi, Olabode (Faculty of Architecture, Planning and Surveying Universiti Teknologi MARA, 2018)
Stakeholders’ attention in construction industry is always drawn to the issue of project performance as more project are characterised by cost over, time over and low quality of work. Different reasons for poor project performance have been identified among which is Construction Manager (CM) skills. This study therefore examines the relationship between CM skills and project performance of cost and time. 88 skills were identified from literatures and these were categorised under six major types; technical, managerial, legal, construction industry and business, people and financial skills. The study was conducted in Lagos state among randomly selected construction firms from sampling frame of Lagos State Tender Board and Building Price Book. Two sets of questionnaires were employed in gathering data for the study. A total of 145 questionnaires were distributed and 106 retrieved and valid for analysis representing 73% response rate respectively. The respondents were majorly CM and their superior. Using Principal Component Analysis with Varimax Rotation, six factors were extracted and a total of 28 skills indicators identified. Mean and Spearman Correlation Analysis were used in analyzing the data. The findings reveal that CMs possess all the identified skills and a significant relationship was found between overall CM skills and project performance of cost and time. It was therefore concluded that the more a CM possesses skills, the higher is the project performance in terms of cost and time. The study recommends that CM should be trained regularly to improve their skills and project performance.